The Rise of the Spirit of National Interest and the Existence of World Trade Organization Agreement: A Case Study of Indonesia - I Gusti Ngurah Parikesit; I Gusti Ngurah Wairocana (Faculty of Law, Universitas Padjadjaran, 2017)
There has been an anxiety over the rise of the spirit of national interest on the existence of World Trade Organization. This spirit that has been reflected from domestic trade policy, to some extent, has undermined trade negotiation process under the WTO as shown by the failure of the Doha Round to conclude significant trade deals. Countries also started concluding bilateral and regional trade agreements instead of the WTO. This article aimed to analyze whether the rise of the spirit of national interest has threaten the existence of the WTO agreements, putting Indonesia as a case study. This article is a normative research, analyzing the dynamics development of the national interest under the WTO, especially Indonesia, and how the judicial body has responded the rise of this spirit in its decisions. This article argues that the spirit of national interest will not threaten the existence of WTO as this spirit has been exist from the early establishment of the General Agreement on Tariffs and Trade in 1947 to the latest WTO negotiation. Moreover, the existence of the WTO judicial body will secure the existence of the WTO, especially because it has successfully controlled the overwhelming spirit of national interest of its members through its decisions. Kebangkitan Semangat Kepentingan Nasional dan Eksistensi Persetujuan World Trade Organization: Studi Kasus Indonesia AbstrakTelah timbul suatu kekhawatiran atas bangkitnya semangat kepentingan nasional terhadap eksistensi persetujuan WTO. Semangat ini yang tercermin dari kebijakan perdagangan domestik telah menghambat proses negosiasi perdagangan di bawah WTO sebagaimana ditunjukkan oleh kegagalan Putaran Doha dalam menyetujui kesepakatan perdagangan. Negara-negara juga mulai menyetujui kesepakatan perdagangan yang lebih bersifat bilateral dan regional. Artikel ini bertujuan untuk menganalisis apakah bangkitnya semangat kepentingan nasional telah mengancam eksistensi kesepakatan WTO, dengan menjadikan Indonesia sebagai studi kasus. Artikel ini adalah penelitian normatif, menganalisis perkembangan dinamika kepentingan nasional di bawah WTO, khususnya Indonesia, dan bagaimana badan judisial merespon bangkitnya semangat ini dalam keputusannya. Artikel ini berpendapat bahwa semangat kepentingan nasional tidak akan mengancam keberadaan WTO karena semangat ini telah ada sejak awal berdirinya GATT di 1947 sampai negosiasi WTO terakhir. Melalui keputusan-keputusan yang telah dihasilkan, keberadaan badan penyelesaian sengketa dalam WTO akan menjamin eksistensi WTO, terutama karena telah berhasil mengendalikan semangat kepentingan nasional dari anggota WTO. Kata kunci: studi kasus, Indonesia, perjanjian internasional, semangat kepentingan nasional, WTO. DOI: https://doi.org/10.22304/pjih.v4n2.a6